Special paperHeart regeneration - Kozar-Kamińska, Katarzyna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Heart failure is the leading cause of death worldwide and the main reason for hospitalization of patients 65-years of age and older. Current therapies only delay progression of the disease but the overall mortality remains as high as 20% per year. The underlying issue is the same whether the cause is acute damage, chronic stress from disease, or aging – progressive loss of functional cardiomyocytes and diminished hemodynamic output. Trials for regenerating cardiac muscle with cell-based therapy are ongoing for more than 10 years now. Multiple candidate cell types have been used in laboratory experiments and I generation clinical trials, including: skeletal myoblasts, bone marrow and peripheral blood mononuclear cells, endothelial progenitor cells, neonatal cardiomyocytes, mesenchymal stem cells, embryonic stem cells, induced pluripotent stem cells and cardiac stem cells. Results of these studies suggest that cell-based therapy for the failing heart can improve cardiac function. More recently, it has been shown that the heart is not terminally differentiated, and resident cardiac stem cells become a potential source for regeneration of cardiac muscle, smooth muscle and endothelium. This paper summarizes the results of I generation clinical trials and discuss prospects of regenerative therapy in the near future, especially in the context of new stem cell populations available.